Economic Education and The Spirit of Pancasila Economy - Hari Wahyono; Muhammad Hasyim Ibnu Abbas; Sri Umi Mintarti Widjaja (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Neglecting the importance of economic education, both in the family environment, social environment, and especially in the arena of formal education can have a negative impact on both the micro and macro levels of economic life. At present the position of students' knowledge of ideology is minimal or they do not understand Pancasila ideology which is fundamental in life, both social, political, legal, and economic activities, therefore the teacher's role is very important in fostering student character and instilling Pancasila ideology from an early age. many economics teachers do not understand the essence of the Pancasila economy. This causes the learning process for students related to the economic insights of Pancasila can also be ascertained to be very lacking. This community service program aims to increase teachers' understanding of Pancasila Economy so that they can apply it in economics lessons in class. The objects in this community service activity are the teachers who are members of the Malang City Economics Teachers Association (MGMP). The many questions that arose during the activity indicated the teachers' interest in the implementation of Pancasila in every economic lesson in their respective classes. From this activity, it appears that many teachers lack an understanding of what the Pancasila Economy is. This is shown by the many questions that come in regarding how to teach Pancasila Economy in schools.